2014
DOI: 10.1007/s10565-014-9289-y
|View full text |Cite
|
Sign up to set email alerts
|

Brominated flame retardants, tetrabromobisphenol A and hexabromocyclododecane, activate mitogen-activated protein kinases (MAPKs) in human natural killer cells

Abstract: NK cells provide a vital surveillance against virally infected cells, tumor cells, and antibody-coated cells through the release of cytolytic mediators and gamma interferon (IFN-γ). Hexabromocyclododecane (HBCD) is a brominated flame retardant used primarily in expanded (EPS) and extruded (XPS) polystyrene foams for thermal insulation in the building and construction industry. Tetrabromobisphenol A (TBBPA) is used both as a reactive and an additive flame retardant in a variety of materials. HBCD and TBBPA cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…Both compounds are able to decrease the lytic function and cell surface protein expression of human NK cells (Hinkson & Whalen, 2009; Hinkson & Whalen, 2010; Kibakaya et al, 2009; Hurd & Whalen, 2011). This inhibition of NK lytic function may be due to their ability to induce activation/phosphorylation of MAPKs and MAP2Ks (Cato et al, 2014). Other environmental contaminants such as tributyltin (TBT) and dibutyltin (DBT) (Kimbrough, 1976) that decrease NK lytic function (Dudimah et al, 2007a,b), while activating the MAPK pathway (Aluoch et al, 2006; Odman- Ghazi et al, 2010), have been shown to alter IFNγ secretion from human immune cells (Lawrence et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both compounds are able to decrease the lytic function and cell surface protein expression of human NK cells (Hinkson & Whalen, 2009; Hinkson & Whalen, 2010; Kibakaya et al, 2009; Hurd & Whalen, 2011). This inhibition of NK lytic function may be due to their ability to induce activation/phosphorylation of MAPKs and MAP2Ks (Cato et al, 2014). Other environmental contaminants such as tributyltin (TBT) and dibutyltin (DBT) (Kimbrough, 1976) that decrease NK lytic function (Dudimah et al, 2007a,b), while activating the MAPK pathway (Aluoch et al, 2006; Odman- Ghazi et al, 2010), have been shown to alter IFNγ secretion from human immune cells (Lawrence et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HBCD and TBPA also differ in their capacity to activate MAPKs. HBCD is able to activate p44/42 while TBBPA activates both p44/42 and p38 (Cato et al, 2014). Thus, at least part of the difference in the effects of these 2 compounds on IFNγ secretion may be due to their ability to differentially activate MAPKs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, TBBPA and HBCD decreased key cell surface proteins and activated MAPKs in NK cells (Hinkson and Whalen, 2010; Hurd and Whalen, 2011; Cato et al, 2014). Additionally, alterations of interferon (IFN)-γ secretion from increasingly re-constituted immune cell preparations such as NK cells, peripheral blood mononuclear cells (PMBC), and monocyte-depleted (MD) peripheral blood mononuclear cells (MD-PBMC) were seen after exposure to TBBPA and HBCD (Almughamsi and Whalen, 2015).…”
Section: Introductionmentioning
confidence: 99%